Perceived Discrimination as a Threat to the Mental Health of Chinese International Students in Australia - Zhao, Jian; Chapman, Elaine; Houghton, Stephen; Lawrence, David (Frontiers in Education, 2022)
In this study, a brief instrument (the Mental Health Change Indicator Scale, MHCIS) was developed for use in assessing the impact of a negative event on mental health. The instrument was then used to compare the reported impact of the COVID-19 pandemic on the mental health of Chinese university students studying either in China (n = 734) or Australia (n = 108). Perceived discrimination and social support were also evaluated as possible mediators of the relationship between country of residence (Australia vs China), and mental health impact. Results suggested that the 10-item MHCIS was unidimensional and psychometrically sound, and that the pandemic had a significantly (p < .001) more negative impact on the mental health of Chinese students studying in Australia than on those studying in China. Perceived discrimination was identified as a key mediating factor in this relationship. Possible implications for higher education institutions in Australia are discussed.